Determination of Nutritive Value and In Vitro Gas Production of Some Triticale Varieties. - Kurt, Özer (My University, 2022)
The aim of this study to determine the chemical composition, in vitro total gas production (TG), metabolisable energy (ME) and organic matter digestibility (OMD) of grains belonging to different triticale varieties. Crude ash (CA) contents of varieties range from 2.05 to 2.30%, ether extract (EE) contents of the varieties is range of 1.82%-3.00%, crude protein (CP) content of varieties between 9.44 and 13.25%, acid detergent fiber (ADF) and neutral detergent fiber (NDF) contents of were range of 2.51-4.50% and 15.15-17.65%, respectively. In vitro total gas production of varieties was between 57.59 and 62.51, ME and OMD also between 11.69-12.55 Mj kg-1 DM and 78.06-82.24%, respectively. While Bera and Tatlıcak 97 leap out in terms of ME, Bera variety leap out in terms of OMD. Effects of varieties on chemical composition, in vitro TG, ME and OMD of triticale grains were found to be significant (P<0.05). According to chemical composition and fermentation parameters, Bera variety, has high values in terms of CP, ME and OMD can be recommended for grain production.